UNDECLINABLE EXPRESSIONS IN LITERARY TRANSLATION FROM POLISH TO MACEDONIAN LANGUAGE (Journal of Contemporary Philology, 2019)
This paper looks at indeclinable words or expressions at discourse level, treating them  as  upgraded  elements  of  propositional  meaning  and  modifiers  of  textual meaning.  Given  their  function,  we  use  the  polish  term modulantsand  apply  the classification of these discourse elements as suggested by Grochowski. The term is accepted in Polish translation science as being common to units of text whose categorical-grammatical  nature  is  diverse:  it  can  include  traditional  particulates, genetic prepositions, some pronouns, often pronouns, evaluative or affective char-acter,  and  even  and  intentional  conjunctions,  as  well  as  whole  language  phrases with  an  established  morphological  structure.  The  analysis  is  based  on  examples from Polish literary works and their equivalents in the Macedonian translation, i.e., on the differences in translation based on the semantic nuances introduced by the modulators.  Language  equivalents  do  not  always  perform  the  same  function, thereby fitting the additional nuances of meaning and causing differences between the original and the translation. Those differences arise either through the use of functionally  misfit  equivalents  or  through  omitting  these  so  called  “facultative” elements, following the wrongly traditional linguistic understanding of their use-fulness for the text. The analysis aims to show exactly the opposite–that is, that they are important for the text and, in particular, for the translation.
Keywords: unchangeable expressions; modulants; terminology; translation; equivalents